Aflatoxins contents determination in some foodstuffs in Burkina Faso and human health risk assessment. (December 2022) - Bandé, Moumouni; Traoré, Inna; Nikiema, Fulbert; Méda, Naamwin-So-Bawfu Romaric; Kpoda, Dissinvel S.; Bazié, Bazoin Sylvain Raoul; Ouédraogo/Kagambèga, Marceline; Ilboudo, Inoussa; Sama, Ouambila Isidore; Compaoré, Abdoul Kiswensida Müller; Meda, Naa-Imwine Stanislas Dimitri; Ouattara Sourabie, Bernadette Pane; et al.
Abstract: Aflatoxins are produced by fungi of the genus Aspergillus that colonize many foodstuffs during agricultural production, harvesting, transportation, storage, and food processing. In view of these aflatoxins toxicity to humans, their presence in foods such as cereals and oilseeds constitutes a major challenge for global food security, health and nutrition. This study was therefore initiated to assess the level of aflatoxin contamination of various foodstuffs sold in urban and semi-urban markets in Burkina Faso, and to evaluate the carcinogenic risk which the consuming population is exposed to. Two hundred and twelve foodstuff samples were collected in two large cities (Ouagadougou and Bobo Dioulasso) and three semi urban localities (Cinkansé, Dakola and Niangoloko). Aflatoxins contents in foodstuffs were determined by immunoaffinity chromatography and human health risk assessment was performed by using the Monte Carlo algorithm. The aflatoxins contents determination showed that 41.50% of studied samples were contaminated with concentrations up to 182.28 μg/kg for AFB1 in peanuts. Chronic Daily Intake, calculated based on the consumption patterns assumed in this study, was estimated to be higher in large cities (CDI = 33.68 μg/kg bw in Ouagadougou and 10.18 μg/kg bw in Bobo Dioulasso) than in semi urban localities (CDI = 4.29 μg/kg bw in Cinkansé, CDI = 0.39 μg/kg bw in Dakola and CDI = 0.18 μg/kg bw in Niangoloko). The MOE determination showed that the sorghum meal and whole grain maize consumption was associated to the carcinogenic risk for public health in large cities (the percentile 95 of MOE = 3316 for rice, 4511 for peanuts, 3334 for sorghum meal and 4530 for whole grain maize). In semi urban localities, no carcinogenic risk was observed to public health. These results should inspire the country's sanitary and agricultural authorities to undertake actions to fight against the agricultural food products contamination by aflatoxins in order to safeguard the population's health. Graphical abstract: Image 1 Highlights: Almost half of the 212 samples analyzed (cereals and legumes) were contaminated with aflatoxins. Population exposure rates to aflatoxins, are higher in the large cities of Burkina Faso. Cereals consumption is associated to a carcinogenic risk for public health in large cities.